(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines distance education as a global phenomenon within educational and information culture in the context of the emerging information society. It analyzes the role of information and communication technologies in transforming the educational process, expanding access to knowledge, and changing traditional forms of learning. The concepts of “distance education” and “distance learning” are distinguished, along with their significance in contemporary educational practice. It is demonstrated that the development of distance technologies contributes to the formation of new pedagogical approaches focused on students’ independent activity, their creative development, and their ability to process information.